Development of a rubber seed processing technology for the production of vegetable oil and animal feed. Phase I. Final report. - UNIDO
Final report on vegetable oils and animal feed production based on processing of rubber oilseeds- (1) surveys relevant literature and documentation (2) presents a field study from Sri Lanka considering technical and economic aspects of producing rubber seed oil and cake (3) covers laboratory research and testing, with attention to: separation and refining; chemical analysis; quality control; storage; oil filtering; composition of rubber seed meal (4) proposed pilot plant trials.
Keywords: Animal feeds; Feed production; Oil seeds; Rubber seed; Rubber seed processing; Vegetable oil